Clinical Characteristics and Outcomes Until 2 Years of Age in Preterm Infants With Typical Chest Imaging Findings of Bronchopulmonary Dysplasia: A Propensity Score Analysis - Ruan, Qiqi; Wang, Jianhui; Shi, Yuan (Frontiers in Pediatrics, 2021)
Objective The goal of the current study was to assess the associations of typical imaging findings of bronchopulmonary dysplasia (BPD) in preterm infants with clinical characteristics and outcomes at 2 years of age. Method This retrospective cohort study enrolled 256 preterm infants with BPD who were admitted between 2014 and 2018. Medical records were retrospectively collected and analyzed. A propensity score analysis was used to adjust for baseline characteristics and a multivariate logistic regression analysis was performed to identify independent variables of mortality. The primary outcomes were the severity of BPD, home oxygen therapy (HOT) at discharge and mortality from 28 days after birth to anticipated follow-up. Results Seventy-eight patients with typical chest imaging findings and 178 patients without typical imaging findings were enrolled. The matched groups consisted of 58 pairs of patients. Those with typical imaging findings has a remarkably higher mortality rate (29.3% vs 12.1%; p=0.022), higher proportion of moderate-severe BPD (56.9% vs 25.9%; p=0.001) and higher rate of HOT at discharge than those without typical imaging findings (74.1% vs 46.6%, p=0.002). The multivariate logistic regression analysis showed that typical imaging findings were an independent risk factor for mortality in preterm infants with BPD (OR 5.140, p<0.001). Conclusions Typical imaging findings were significantly related to poor outcomes of BPD. More attention should be given to radiographic patterns of BPD in preterm infants.